THE INFLUENCE OF SOCIAL INEQUALITY ON THE CHARACTER OF KIM KI TAEK ON PARASITE FILM - Popy Khairunnisa; Bima Prana Chitra (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2021)
THE INFLUENCE OF SOCIAL INEQUALITY ON THE CHARACTER OF KIM KITAEK ON PARASITE FILMPopy Khairunnisa1, Bima Prana Chitra2Fakultas Bahasa dan KomunikasiUniversitas Harapan MedanEmail: popykhairunnisa98@gmail.comABSTRACTThe objectives of this research are personality traits of Kim Ki Taek character possess, socialinequality affect to Kim Ki Taek’s life and moral values presented in Parasite film. This researchused descriptive qualitative research. The data of this research were script, character and film onParasite film (2019) as the source of data. This research focuses on personality trait of Kim KiTaek's character based on theory of McCrae and Costa (1990), social inequality problemsexperienced by Kim Ki Taek's character based on Abad Badruzaman (2009: 284) and moralvalues in film “parasite” based on Wantah (2006). The results of this research were (1)personality traits of Kim Ki Taek character were oppeners and neuroticism but is low inagreeableness, (2) Social inequality of Kim Ki Taek character were social inequality – economy,(3) Moral values of “Parasite” film were Moral Ethics and Decency.Keywords: Personality Traits, Social Inequality, Poverty, Moral.